Cancer: A Very Short Introduction - James, Nicholas (New York Oxford University Press, 2011)
In 1961 John F. Kennedy pledged to put a man on the moon by the end of the decade. Nine years later, Neil Armstrong and Buzz Aldrin walked on the moon. Ten years later, Richard Nixon echoed this pledge by declaring a 'war' on cancer. More than 30 years later, however, cancer remains one of the largest causes of death worldwide, with around 1 in 3 developing the disease. Curing cancer is not 'rocket science', but the question is, why has cancer proved to be harder to tackle than themoon landings turned out to be? Cancer research is a major economic activity. There are constant improvements in t
Includes Index and Illustrations.
Keywords: Cancer -- Popular works